2019
DOI: 10.1002/slct.201803600
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Separable Transition Metal Ferrites: Versatile Heterogeneous Nano‐Catalysts for the Synthesis of Diverse Bioactive Heterocycles

Abstract: This review compiles the up to date literatures on the preparations and applications of the transition metal ferrites as an efficient, heterogeneous, magnetically separable nano‐catalyst for the synthesis of diverse bioactive heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 123 publications
0
13
0
2
Order By: Relevance
“…All the melting points were recorded by open capillary method and are uncorrected. 1 H NMR and 13 C NMR spectra were recorded on a Bruker Avance (250 MHz) spectrometer using CDCl3 as the solvent and TMS as an internal standard. Thin-layer chromatography (TLC) was performed on precoated aluminium plates (silica gel 60 F254, Merck).…”
Section: Methodsmentioning
confidence: 99%
“…All the melting points were recorded by open capillary method and are uncorrected. 1 H NMR and 13 C NMR spectra were recorded on a Bruker Avance (250 MHz) spectrometer using CDCl3 as the solvent and TMS as an internal standard. Thin-layer chromatography (TLC) was performed on precoated aluminium plates (silica gel 60 F254, Merck).…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of pyrazoles. Gharib et al reported a facile protocol for the efficient synthesis of a series of pyrazole derivatives (22) from the reactions of various hydrazine derivatives (21) and 1,3-diketones (20) in the presence of Preyssler heteropoly acid (H14[NaP5W30O110]) as catalyst in water at room temperature (Scheme 8). 82 The solid heterogeneous catalyst was recovered easily and reused for five successive runs.…”
Section: Author(s)mentioning
confidence: 99%
“…Magnetic nanoparticles are the particles group of heterogeneous catalysts with small size and highly active surface area. This catalyst was applied in different fields such as technological, medical, pharmacology, drug delivery and catalyst .…”
Section: Introductionmentioning
confidence: 99%